2016
DOI: 10.1111/eci.12703
|View full text |Cite
|
Sign up to set email alerts
|

Male, old age and low income to predispose epilepsy in migraineurs

Abstract: Migraineurs have an increased risk of subsequent epilepsy. Male sex, old age and low income may interact with migraine and result in a high risk of epilepsy in migraineurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…One such study evaluated the risk of developing subsequent epilepsy when first diagnosed with migraine and found that individuals with migraine and those who had migraine and sleep disorders, cognitive disorders, anxiety or depression were more likely to develop epilepsy than healthy individuals 30 . This cohort was followed-up for a mean period of 12 years, and the relative risk of developing epilepsy was found to be 2.3 times higher in men than in women 31 . Risk was increased by older age, low-income status and comorbidities, especially head trauma.…”
Section: [H2] a Bidirectional Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…One such study evaluated the risk of developing subsequent epilepsy when first diagnosed with migraine and found that individuals with migraine and those who had migraine and sleep disorders, cognitive disorders, anxiety or depression were more likely to develop epilepsy than healthy individuals 30 . This cohort was followed-up for a mean period of 12 years, and the relative risk of developing epilepsy was found to be 2.3 times higher in men than in women 31 . Risk was increased by older age, low-income status and comorbidities, especially head trauma.…”
Section: [H2] a Bidirectional Relationshipmentioning
confidence: 99%
“…For example, the risk of developing epilepsy was 4.6 times higher in men with migraine and a history of head trauma than in men with migraine and no history of head trauma 31 . These studies are longitudinal, but only assessed the risk of developing epilepsy in people with migraine and do not provide information on whether or not the relationship is truly bidirectional.…”
Section: [H2] a Bidirectional Relationshipmentioning
confidence: 99%